Epicardial adipose tissue in patients with chronic obstructive pulmonary disease: systematic review with meta‑analysis and trial sequential analysis - Lan, Yi; Ma, Qianli; Luo, Guangming; Yang, Heping; Li, Yingrui; Zhang, Qiao (BMC pulmonary medicine, 2023)
Background Limited data suggest that chronic obstructive pulmonary disease (COPD) patients have pathologic elevated epicardial adipose tissue (EAT), which is splanchnic fat tissue with anti-inflammatory properties and regulating free fatty acids functions. Therefore, there is a need for meta-analysis to explore the relationship between EAT and COPD. Methods Online databases were systematically searched for studies about EAT in COPD patients published up to October 5th, 2022. The EAT data of the COPD patient group and the control group were included. Trial sequential analysis (TSA) and meta-analysis were applied to assess the difference in EAT between patients with and without COPD. TSA software and Stata 12.0 were used in all statistical analyses. Results The final analysis included 5 studies (n = 596 patients). COPD patients had significantly more EAT than control subjects (SMD: 0.0.802; 95% CI: 0.231, 1.372; P = 0.006; TSA-adjusted 95% CI 1.20, 1.80; P < 0.0001). And higher CRP levels in COPD patients than non-COPD patients, whereas triglycerides and LDL were not significantly different between patients with and without COPD. Conclusion EAT is abnormally elevated in COPD patients, which may be related to systemic inflammatory responses in COPD. PROSPERO number CRD42021228273.